Role of Anthropometric Nutritional Assessment in Severe Head Injury - Dhandapani, Manju; Dhandapani, Sivashanmugam; Agarwal, Meena; Chutani, Alka; Sharma, Bhawani S.; Mahapatra, Ashok K. (Indian Journal of Neurotrauma, 2019)
Aim Nutritional demand after traumatic brain injury is increased due to hypermetabolic response. The present study was undertaken to assess nutritional status with anthropometric indices, factors associated, and their prognostic role following severe head injury (SHI).Method A total of 114 patients in age group 20 to 60 years, admitted within 24 hours of SHI, with Glasgow Coma Scale of 4 to 8, and with no serious systemic disorder were enrolled for the study. Of these, 67 were prospectively assessed weekly till 21 days for changes in mid arm circumference (MAC), mid arm muscle circumference (MAMC), and triceps skin fold thickness (TSF). They were studied in relation to other factors and outcome was assessed at 3 months.Results The percentage fall at 3 weeks for MAC, MAMC, and TSF were 14, 10, and 37%, respectively. The percentage of fall in MAMC was the earliest, and was significantly greater in patients with surgical intervention, tracheostomy, prolonged fever, delayed enteral feeding, and greater caloric deficit. Admission MAMC < 90% of standard was significantly associated with unfavorable outcome (odds ratio 5.9 [95% confidence interval 1.3–27.8], p = 0.01). Unfavorable outcome was significantly more frequent in patients who had at least 15% fall in MAC (85.7 vs. 41.9%, p = 0.03), or 10% fall in MAMC (68.8 vs. 38.2%, p = 0.04) at 2 weeks, compared with others. Fall in TSF had no significant association with outcome at 3 months. In multivariate analysis, MAMC fall had significant independent association with unfavorable outcome.Conclusion Bedside anthropometry (especially MAMC) is efficient in identifying patients with nutrition depletion with significant influence on outcome at 3 months.
Keywords: severe head injury; nutritional assessment; anthropometry; outcome